2018
DOI: 10.1186/s12905-018-0553-9
|View full text |Cite
|
Sign up to set email alerts
|

Emotional violence and maternal mental health: a qualitative study among women in northern Vietnam

Abstract: BackgroundWorldwide, intimate partner violence (IPV) during pregnancy is a pressing and prevalent public health problem. Existing research has found close associations between IPV and perinatal mental health, yet little is known about women’s own perceptions of these associations. This study aimed to explore Vietnamese women’s experiences of emotional partner violence and their perceptions of the implications of such violence for their mental health.MethodsThe data were collected through in-depth interviews wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 30 publications
1
24
0
5
Order By: Relevance
“…Other studies report the possibility of changes in risk behavior that may result from violence (such as alcohol intake and smoking), which also aggravate the risk of PPD [ 34 ]. Another explanation for the findings may be that exposure to emotional violence coexists in settings with a high level of dysfunctional family relations, including lack of partner support, which also may result in responses such as psychological problems [ 35 ]. This could be explained by the dynamics of maternity care in the cultural context of Vietnam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies report the possibility of changes in risk behavior that may result from violence (such as alcohol intake and smoking), which also aggravate the risk of PPD [ 34 ]. Another explanation for the findings may be that exposure to emotional violence coexists in settings with a high level of dysfunctional family relations, including lack of partner support, which also may result in responses such as psychological problems [ 35 ]. This could be explained by the dynamics of maternity care in the cultural context of Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…In northern Vietnam, women who get married will most often leave their natal families and move to live with or nearby their husband’s family (marriages are patrilocal) [ 35 ]. The majority of women in our study had moved into the house of their husband’s family after getting married.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from across the world indicated that women who were suspected of infidelity also experienced psychological IPV, including being insulted [88,93,100], threatened [89,92] and ignored [96,102] In some studies, men reported facing pressure from their peers to have sex with many women to affirm their masculinities; men who did not have multiple partners were reportedly described as "controlled by their wives" or "cowards" [84,91]. Hence, women asking their partners to be faithful or accusing them of infidelity constituted a direct threat to their aspired masculinities, which was interpreted to have implications for the IPV that followed.…”
Section: Identified Mechanisms and Pathways From Infidelity And Rj Tomentioning
confidence: 99%
“…A widespread finding was that men often used controlling behaviours to limit woman's autonomy and prevent infidelity. Participants reported that men controlled their partners by destroying their property [84], monitoring and restricting their access to text messages, calls and social media [84,91,96,101], frequently calling them to monitor their movements [91,96,100], isolating them from friends and family [84,92,96,100] and in extreme cases, not allowing them to leave the house [92,96]. As a midwife described:…”
Section: Identified Mechanisms and Pathways From Infidelity And Rj Tomentioning
confidence: 99%
See 1 more Smart Citation